The Ethics of Mystical Journeying in Yogic Mysticism - Ali Sadeqi Shahpar (اخلاق وحیانی)
Very much like other mystical practices in India, the Pantanjali Yoga mysticism has also made use of Indian ethics and religion as well as the ethical laws of Mano in its primary stages of mystical journey.There are eight stages of mystical journey in the yoga tradition, in which, the first two stages concern ethical conduct and the Indian worships and religion practices which are done in order to achieve mystic meditation and yogic liberation. Each of these two stages consists of five moral and religious laws. Ahimsa (meaning “not to injure”), which is one of the principles shared by all Indian religions and philosophical schools of thought, is considered to be the axis of ethics, and a person, who has become perfect in Ahimsa, is considered to have perfected in ethics and such a person is, then, authorized to go to the next stages of mystical journey which are beyond ethics and objective issues. This paper seeks to examine the yogic and Indian ethics with a focus on the first two stages of the eight-stage yogic mystical journey.